2017
DOI: 10.1111/desc.12572
|View full text |Cite
|
Sign up to set email alerts
|

Iconicity in the speech of children and adults

Abstract: Iconicity - the correspondence between form and meaning - may help young children learn to use new words. Early-learned words are higher in iconicity than later learned words. However, it remains unclear what role iconicity may play in actual language use. Here, we ask whether iconicity relates not just to the age at which words are acquired, but also to how frequently children and adults use the words in their speech. If iconicity serves to bootstrap word learning, then we would expect that children should sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 44 publications
8
111
2
2
Order By: Relevance
“…This tendency toward iconicity in IDS applies more generally to other words addressed to infants in both spoken and signed languages. For example, words used in English IDS, including those that are not specifically onomatopoeic, receive higher overall iconicity ratings than those in ADS (Perlman, Fusaroli, Fein, & Naigles, 2017;Perry, Perlman, Winter, Massaro, & Lupyan, 2017). In British Sign Language, signs with transparent iconicity are further modified in infant-directed language in a way that highlights the nonarbitrary gesture-meaning mapping (Perniss, Lu, Morgan, & Vigliocco, 2017).…”
Section: Iconicitymentioning
confidence: 99%
See 1 more Smart Citation
“…This tendency toward iconicity in IDS applies more generally to other words addressed to infants in both spoken and signed languages. For example, words used in English IDS, including those that are not specifically onomatopoeic, receive higher overall iconicity ratings than those in ADS (Perlman, Fusaroli, Fein, & Naigles, 2017;Perry, Perlman, Winter, Massaro, & Lupyan, 2017). In British Sign Language, signs with transparent iconicity are further modified in infant-directed language in a way that highlights the nonarbitrary gesture-meaning mapping (Perniss, Lu, Morgan, & Vigliocco, 2017).…”
Section: Iconicitymentioning
confidence: 99%
“…These effects are also found in naturalistic vocabulary development. Early‐acquired words tend to be more iconic than later‐acquired words both in spoken languages (Massaro & Perlman, ; Perlman et al., ; Perry, Perlman, & Lupyan, ; Perry et al., ) and sign languages (Caselli & Pyers, ; Thompson, Vinson, Woll, & Vigliocco, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both adults and children memorize more easily novel soundmeaning mappings when the pseudowords are sound symbolic compared to when they are not, suggesting that sound symbolism facilitates word learning processes Imai, Kita, Nagumo, & Okada, 2008;Kantarzis, Imai, & Kita, 2011;Monaghan et al, 2012). Similarly, more recent findings demonstrate that compared to adults, young children hear and tend to produce sound symbolic words more frequently than non-symbolic words in their spontaneous speech (Perry, Perlman, Winter, Massaro, & Lupyan, 2017). However, whether the sensitivity to sound symbolic relationships in language is present in their earliest stages of life (Ozturk, Krehm, & Vouloumanos, 2013;Peña, Mehler, & Nespor, 2011;Spector & Maurer, 2009;Walker et al, 2010Walker et al, , 2014 or emerges as a consequence of exposure to cross-modal statistical regularities in the environment (Fernández-Prieto, Navarra, & Pons, 2015; Lewkowicz & Ghazanfar, 2009;Lewkowicz & Minar, 2014) remains a matter of debate.…”
mentioning
confidence: 98%
“…In combination with other recent work (e.g., Auracher, 2017;Perlman et al, 2015;Perry et al, 2018;Westbury et al, 2018), we hope that the present investigation helps to move us beyond the simple question of whether people make use of non-arbitrary relationships in spoken language (they do!) and toward understanding why natural languages are not even more iconic Monaghan et al, 2014) and precisely where the form-meaning associations used by our participants came from.…”
Section: Discussionmentioning
confidence: 56%
“…Although these investigations of sound symbolism have not settled the question of where these associations between forms and meanings come from (but see Imai & Kita, ; Sidhu & Pexman, ; Spence, ), they have further demonstrated the varied way in which iconicity plays a role in language learning and vocal communication. For example, Perry, Perlman, Winter, Massaro, & Lupyan, () showed that more iconic words are learned earlier by children (adjusting for numerous potential confounds like frequency, concreteness, and communicative need; see also, e.g., Imai, Kita, Nagumo, & Okada, ; Maurer et al, ; Peña, Mehler, & Nespor, ; for further review, see Imai & Kita, ). Such apparent advantages of iconicity go beyond word‐learning.…”
Section: Introductionmentioning
confidence: 99%